2000
DOI: 10.1046/j.1472-765x.2000.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of inactivated probiotic strains to intestinal mucus

Abstract: It has been suggested that probiotics should be viable in order to elicit beneficial health effects. Inactivation of probiotics has been suggested to interfere with the binding to the mucosa and thereby with the immune modulating activity of probiotics. The effect of different inactivation methods on the mucus adhesion of nine probiotic strains was studied. Inactivation by heat or γ‐irradiation generally decreased the adhesive abilities. However, heat treatment increased the adhesion of Propionibacterium freud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 19 publications
5
88
0
3
Order By: Relevance
“…Both probiotic strains studied in this work displayed similar coaggregation with the pathogen C. jejuni CIP 70.2 T , regardless of whether they had been heattreated. Inactivation by heat has been shown previously to generally decrease the adhesion of probiotic bacteria (Ouwehand et al, 2000) but a similar improvement of adhesion to that described in our study has also been demonstrated for a strain of Propionibacterium freudenreichii (Ouwehand et al, 2000). The reason why adhesion is improved after heat treatment has not yet been elucidated but it may be due to the nature of the molecules involved.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both probiotic strains studied in this work displayed similar coaggregation with the pathogen C. jejuni CIP 70.2 T , regardless of whether they had been heattreated. Inactivation by heat has been shown previously to generally decrease the adhesion of probiotic bacteria (Ouwehand et al, 2000) but a similar improvement of adhesion to that described in our study has also been demonstrated for a strain of Propionibacterium freudenreichii (Ouwehand et al, 2000). The reason why adhesion is improved after heat treatment has not yet been elucidated but it may be due to the nature of the molecules involved.…”
Section: Discussionsupporting
confidence: 88%
“…It was observed for example that there was a dramatic decrease in the adhesive ability of Lb. rhamnosus GG whatever the intestinal matrix model (Tuomola et al, 1999) or on Caco-2 cells (Ouwehand et al, 2000). The reduction of adhesion can be explained by the heatsensitive proteinaceous nature of the molecules involved in Lb.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface hydrophobicity was determined according to the capacity of the four selected strains and the five indicator strains to individually partition into xylene from PBS (Ouwehand et al 1999). The cells were washed twice with PBS and the optical density (A) at 450 nm adjusted to 0.5 ± 0.01.…”
Section: Cell Surface Hydrophobicitymentioning
confidence: 99%
“…Selection of potential probiotic strains is based on many different criteria, such as acid and bile tolerance (tolerance to gastrointestinal environment), antagonistic activity against pathogens and survival in gastric juice. Adhesion of probiotic microorganism to the intestinal mucosa is considered important for many of the observed probiotic health effects (Ouwehand et al 1999). Adhesion is regarded a prerequisite for colonization in the fishes intestinal tract, antagonistic activity against enteropathogens, modulation of the immune system and for increased healing of the damaged gastric mucosa (Rinkinen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This process is thought to enhance mucosal damage and intestinal inflammation related to gut RT (5)(6)(7)(8).…”
mentioning
confidence: 99%